Keadilan Gender dalam Maqasid Al-Syari’ah : Pendekatan Feminisme Islam - Siagian, Nakhla Isfina; Rahmawati , Anisa; Hasan , Tazkiyya Ibnatu (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This article examines the perspective of gender justice within the context of Maqasid al-Shari’ah, a central concept in Islamic legal thought. Using a normative-critical approach, this paper evaluates how the concept of Maqasid can serve as a normative principle in addressing gender injustice in contemporary Muslim societies. The main focus of this discussion is the reinterpretation of Maqasid by modern intellectuals that integrates the values of equality and social justice, as well as its relevance to women’s rights.